Visitors Attitude on Servicescape Excelso Societe Surabaya - Rr. Aulia Zerlina Maheswari; Inri Inggrit Indrayani; Felicia Goenawan (Journal of Content and Engagement, 2024)
This research was conducted with the aim of identifying visitors' attitudes towards ExcelsoSociete's servicescape. Marketing public relations creates a memorable experience forvisitors, so Excelso Societe has a strategy to communicate value and become a differentiatorfrom competitors which creates a response in the form of a positive attitude. Brand identity isimportant to achieve company value in introducing products/services. One way to meetconsumer needs is to improve the customer experience through the physical environment.The physical environment or servicescape is an important factor for companies in meetingconsumer needs by providing customer experience.Servicescape becomes a strong communication channel between the brand and the public.Good communication with visitors helps Excelso Societe understand the wants and needs ofvisitors. Public relations is very important in the process of achieving Excelso Societe's goalof building a positive image to visitors. The company's image can be built based on visitors'experiences and perceptions. Consumer attitudes towards a positive image will strengthen thebrand's position in gaining the trust of visitors.The type of research used is descriptive quantitative and uses a survey method. Theresults showed that the spatial layout & functionality dimension obtained the highest score oncognitive attitudes and affective attitudes, while the signs, symbols, and artifacts dimensionobtained the highest score on conative attitudes.